Clinical characteristics and risk factors for severe COVID-19 infections in Malaysia: A nationwide observational study - Benedict Lim Heng Sim, MRCP; Suresh Kumar Chidambaram, MRCP; Xin Ci Wong, MDataSc; Mohan Dass Pathmanathan, MD; Kalaiarasu M. Peariasamy, FDSRCS; Chee Peng Hor, MSc; Hiu Jian Chua, MRCP; Pik Pin Goh, FRCS (Elsevier, 2020)
Summary: Background: COVID-19 emerged as a major public health outbreak in late 2019. Malaysia reported its first imported case on 25th January 2020, and adopted a policy of extensive contact tracing and hospitalising of all cases. We describe the clinical characteristics of COVID-19 cases nationwide and determine the risk factors associated with disease severity. Method: Clinical records of all RT-PCR confirmed COVID-19 cases aged ≥12 years admitted to 18 designated hospitals in Malaysia between 1st February and 30th May 2020 with complete outcomes were retrieved. Epidemiological history, co-morbidities, clinical features, investigations, management and complications were captured using REDCap database. Variables were compared between mild and severe diseases. Univariate and multivariate regression were used to identify determinants for disease severity. Findings: The sample comprised of 5889 cases (median age 34 years, male 71.7%). Majority were mild (92%), and 3.3% required intensive care, with 80% admitted within the first five days. Older age (≥51 years), underlying chronic kidney disease and chronic pulmonary disease, fever, cough, diarrhoea, breathlessness, tachypnoea, abnormal chest radiographs and high serum CRP (≥5 mg/dL) on admission were significant determinants for severity (p<0.05). The case fatality rate was 1.2%, and the three commonest complications were liver injuries (6.7%), kidney injuries (4%), and acute respiratory distress syndrome (2.3%). Interpretations: Lower case fatality rate was possibly contributed by young cases with mild diseases and early hospitalisation. Abnormal chest radiographic findings in elderly with tachypnoea require close monitoring in the first five days to detect early deterioration.